Effect of elastic oral appliance chewing on frontal lobe activity - Yuu Yamamoto; Masahiro Ryu; Takayuki Ueda; Yoshinori Sasaki; Kaoru Sakurai (Wiley, 2023)
Abstract Objectives Chewing increases frontal lobe activity, resulting in improved memory, learning ability, and response reaction time. This study aimed to assess the effects of elastic oral appliance chewing on the activities and functions of the frontal lobe. Methods The study participants were 15 healthy men with full dentulous (mean age, 27.4 ± 4.1 years). A prospective crossover design was used to assess frontal lobe activities and functions. Changes in frontal lobe activities were measured with near‐infrared spectroscopy (NIRS). At baseline, the participants were assessed in the resting state. Changes in channels #7, representing right frontal lobe activities by NIRS, and #10, representing left frontal lobe activities, during the first and second chewing periods in a total of two periods were evaluated. Frontal lobe functions were measured using the Trail Making Test Part A (TMT‐A) in the resting state and after elastic oral appliance or gum chewing. These values were compared with each period. Results Elastic oral appliance chewing caused significant differences between the baseline and first chewing periods for channel #7 (p = .032) and significant differences between the baseline and second chewing periods for channels #7 and #10 (p < .001 and p < .001, respectively) using NIRS. Moreover, significant differences were found in the TMT‐A results between the resting state and elastic oral appliance chewing (p = .04). Conclusions Elastic oral appliance chewing improves frontal lobe activities to a level similar to that obtained with gum chewing.